2015
DOI: 10.1007/s12032-015-0706-8
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of Sirt1 contributes to chemoresistance and indicates poor prognosis in serous epithelial ovarian cancer (EOC)

Abstract: Ovarian cancer is the most lethal malignancy in female patients, and chemoresistance is the major contribution to low over survival rate. We aim to investigate the correction between Sirt1 expression and chemoresistance in serous epithelial ovarian cancer (EOC) and prognosis significance of Sirt1. Immunochemistry was used to determine the location pattern and expression of Sirt1 in a total of 63 serous EOC patients (28 cases of chemoresistance patients and 35 chemosensitive).The relationship between Sirt1 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 22 publications
0
43
1
Order By: Relevance
“…28 Conversely, Chen et al 50 indicated that miR-181a sensitized human malignant glioma cells to radiation; however, the role of miR-181a in human glioma chemoresistance, and more importantly, the downstream target and regulation mechanism that miR-181a regulated human glioma tumorigenesis, still needed more exploration. 33,34 Our sample analysis identified that the expression of miR-181a was lower in tumors than nontumor tissues. 30,35,37,42 These effects have been linked to cell behaviors, involving cell growth, differentiation, migration, and survival.…”
Section: Discussionmentioning
confidence: 97%
“…28 Conversely, Chen et al 50 indicated that miR-181a sensitized human malignant glioma cells to radiation; however, the role of miR-181a in human glioma chemoresistance, and more importantly, the downstream target and regulation mechanism that miR-181a regulated human glioma tumorigenesis, still needed more exploration. 33,34 Our sample analysis identified that the expression of miR-181a was lower in tumors than nontumor tissues. 30,35,37,42 These effects have been linked to cell behaviors, involving cell growth, differentiation, migration, and survival.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that a decline in energy metabolism may play an important role in activating the cell death pathway and dysregulation of pyruvate kinase M2 (PKM2), which favor both carcinogenesis and the Warburg effect [17]. Previous study demonstrated that SIRT1 overexpression is associated with poor outcome and chemo-resistance in ovarian cancer of epithelial origin over-expression, and one of the mechanisms may involve the dysregulation of energy metabolism and stress response [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients with SIRT1-positive liver cancer have a lower survival rate than those with SIRT1-negative liver cancer (38). Overexpression of SIRT1 has been demonstrated to contribute to chemoresistance in serous epithelial ovarian cancer, where it may be a potential prognostic indicator for patient survival outcome (39). SIRT1 is one among other genes involved in DNA repair that are upregulated in platinum-resistant epithelial ovarian cancer (40).…”
Section: Discussionmentioning
confidence: 99%